"A rising tide floats all boats": The role of neighborhood collective efficacy in responding to child maltreatment. (February 2022) - Spilsbury, James C.; Dalton, Jarrod E.; Haas, Bridget M.; Korbin, Jill E.
Abstract: Background: Nearly one-quarter of the approximately 400, 000 reports to child protective services originating from non-mandated reporters come from neighbors. Understanding factors leading non-mandated reporters to contact authorities is important because if modifiable, they might serve as intervention targets to promote reporting of suspected maltreatment. Objective: Investigate associations between neighbors' reported responses to scenarios involving children in need, child/teen misbehavior, and suspected maltreatment with individual and neighborhood characteristics, including neighborhood collective efficacy, fear of victimization, and fear of retaliation. Hypothesis: Increased collective efficacy would be associated with increased likelihood of neighbors taking action in response to the situation. Participants & setting: 400 caregivers of minors in Cleveland, OH, USA living in 20 census tracts. Methods: Generalized linear mixed-effects modeling. Results: Analyses adjusted for covariates confirmed our primary hypothesis: a 1-unit increase in the collective efficacy measure was associated with a 64% increase in the odds of neighbors taking action compared to doing nothing (odds ratio = 1.64, 95th percentile confidence interval 1.41–1.92). Also, participants with less than a high-school education had 36% greater odds of reporting their neighbors taking action compared to more educated participants. An interaction effect between participants' fear of victimization in their neighborhood, but not fear of retaliation, was also observed: the effect of collective efficacy on the odds of neighbors taking action was substantially greater among residents expressing moderate and high fear of victimization. Conclusion: Enhancing collective efficacy may be an effective strategy for fostering community response to suspected child maltreatment and other situations of a child in need because it may catalyze a variety of positive responses to these situations.